Accommodative Response to Asymmetrical Accommodative Stimuli - Vasili Marshev; Jean-Louis de Bougrenet de la Tocnaye; Vincent Nourrit (Vision)
Recent advancements in head-up-displays have increased the number of instances where the visual system may face a different accommodative demand for each eye. A limited number of studies on aniso-accommodation exist, reporting contradictory results. We tested the natural capacity of observers to aniso-accommodate anisometropic stimuli. A dichoptic task allowed us to account for certain confounds, including high-level accommodation control. A 2AFC visual task was used, where participants judged if two overlapping sinusoidal gratings, presented dichoptically, had the same orientation. The gratings’ spatial frequency could be 1, 4 or 10 c/deg. The accommodative demand for each eye could be independently set to 2D or 4D. The accommodative response for each eye was recorded using an autorefractometer. Higher spatial frequencies and anisometropy had a negative impact on task accuracy. Contrary to expectations, spatial frequencies had no significant impact on accommodation response. The accommodation response to anisometropic stimuli was equal in the two eyes and leaned toward the lower of two demands. Our results confirm that when presented with asymmetrical accommodation demand, the two eyes tend to keep the same refractive power even in a dichoptic-requiring task. They also contradict the guidance of accommodation by spatial frequency in sinusoidal gratings. The visual task provided an objective measure of subjects’ performance, allowing for these conclusions to be drawn.